Treatment of Acute Tacrolimus Toxicity with Phenytoin in Solid Organ Transplant Recipients - Arin S. Jantz; Samir J. Patel; Wadi N. Suki; Richard J. Knight; Arvind Bhimaraj; A. Osama Gaber (Case Reports in Transplantation)
The pharmacokinetics of tacrolimus are influenced by many factors, including genetic variability, acute infections, liver dysfunction, and interacting medications, which can result in elevated concentrations. The most appropriate management of acute tacrolimus toxicity has not been defined though case reports exist describing the therapeutic use of enzyme inducers to increase tacrolimus metabolism and decrease concentrations. We are reporting on the utilization of phenytoin to assist in decreasing tacrolimus concentrations in a case series of four solid organ transplant recipients with acute, symptomatic tacrolimus toxicity presenting with elevated serum creatinine, potassium, and tacrolimus trough concentrations greater than 30 ng/mL. All four patients had the potential causative agents stopped or temporarily held and were given 300 to 400 mg/day of phenytoin for two to three days. Within three days of beginning phenytoin, all four patients had a decrease in tacrolimus concentration to less than 15 ng/mL, a return to or near baseline creatinine concentration, and lack of phenytoin-related side effects. Therefore, phenytoin appears to be a safe and potentially beneficial treatment option in patients with symptomatic tacrolimus toxicity.